O Sistema SAEB e as relações de poder - Sousa, Maria do Carmo (2012)
The State believes that education is essential to building a company dedicated to ethical values essential to the construction of citizenship and social justice. It is understood that a society whose guiding principles do not lead to these values hardly evolve fully. It is known that in a globalized world, fully aligned to the interests of capitalism, nations need to demonstrate the effectiveness of their education systems for the production chain. A country, where education does not correspond to the interests of the multilateral organizations and the World Bank is struggling to subsidize it. Hence the main reason that the federal government to initiate education policies aimed at "improving" the quality of teaching. These are actions to bring about change in Brazilian education. It is understood that the PCNs, Evaluation System (SAEB) represent important actions of the government, directly linked to the quality of education. SAEB defines the quality of Brazilian education is good or bad. It happens that the discourse underlying its materiality linguistic forms an order of meaning totally contrary to what is proposed. The speech is a basic element in the maintenance of power relations. The hypothesis is that by SAEB, the State, to respond to the interests described herein creates a control mechanism, which confirms the relationship of inequality and subordination. It aims to show that SAEB, as you conceives as the main instrument capable of measuring the quality of education in Brazil, reflects the policies of closure, now underway, establishing itself as a control mechanism of power and exclusion. In order to sort out some details that escape the observation of society, but that are important to understand what is hidden behind the discourse of the Federal government on the SAEB, we chose to search for a document analysis. Among the works considered important for research on the subject, it was decided by the set of linguistic materiality SAEB System (2008, 2009, 2011), the PCN of the Portuguese Language (1997, 1998, 2006) as readings give information on the corpus, and the texts of Gregolin (2007), Orlandi (2001, 2005), Smith (1996), Foucault (1999, 2006, 2008) Bakhtin (1997) among others, as illustrative readings for corpus analysis. Talks are on the History of Teaching Portuguese Language in Brazil, in order to understand how was the process of language acquisition in this country throughout its history and reveal how the language has always been used in favor of maintaining relationships of power. Lance is also a look at the theory of Bakhtin and the appropriation there of made by PCNs. Contrast to the theoretical assumptions of this author with those who have these documents. From these initial reflections addresses the research corpus. From the perspective of discourse analysis of French, we discuss about the SAEB on its effects on education in Brazil, presenting a different reading of what the MEC is the meaning of the assessments SAEB.